Jeff Wand interviewed by Rob Willis in the Rob and Olya Willis folklore collection - Wand, Jeff, 1930-; Willis, Rob, 1944-; Australian Bullock Drivers' League (2008)
Folkloric recording. Jeff Wand discusses his early life in the Wyong area; the occupations of his parents and grandparents; his love of bullocks and lessons learnt from older bullockies; methods on driving bullocks, the composition and training of the teams; his time in the coal mines; his later business ventures; traditional Australian bullockies today.
Recorded by John Harpley.
Recorded on December 6, 2008 at Cardiff, N.S.W.
Digital master available
There are approx. 5 traditional bullockies in Australia according to the Australian Bullock Drivers' League.
Timed summary (3 p.)
Keywords: Wand, Jeff, -- 1930- -- Interviews; Bullockies -- New South Wales -- Interviews; Bullockies -- Australia; Businessmen -- Australia -- Interviews; Bullockies; Business professionals